On the anisotropy in the dry-sliding behaviour of a self-lubricating PTFE composite and the effects from surface texturing. Issue 5 (4th May 2022) - Ding, Liang; Liao, Zhirong; Butler-Smith, Paul; Colton, Michael
ABSTRACT: In self-lubricating sliding contact facilitated with polytetrafluoroethylene (PTFE) composites, the anisotropy in tribological performance was often attributed to the oriented structures of the polymer. However, in this research, it is found that the non-homogeneity introduced by the hard fibres or stiffeners may be the main contributor to the anisotropic tribological performance of the polymeric composites. The interaction between the non-uniformly arranged hard fibres/stiffeners and the metallic counterface was found to be the leading phenomenon of this tribological behaviour. Moreover, the effects from a surface texturing scheme was found capable of establishing intervention to this interaction and reducing the anisotropy. The mechanism of the texturing effects was found related with back-transfer of PTFE and trapping of wear debris. Graphical abstract: uf0001